Implementasi Aspek Kokurikuler Pramuka dalam Membentuk Karakter Disiplin Siswa - Ibrahim, Ibrahim; Pratiwi, Adelia; Niswah, Choirun (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the implementation of the co-curricular aspects of Scouting in shaping students' disciplinary character at SMA Negeri 3 Palembang. It employs a qualitative research method with a descriptive approach. Data collection techniques include interviews, observations, and documentation. The study involves 13 informants selected using purposive sampling. Data analysis is conducted through data collection, presentation, verification, and conclusion drawing, with data validity ensured through triangulation. The findings indicate that the implementation of co-curricular Scouting activities in fostering student discipline has been well-executed through the stages of planning, implementation, and evaluation. Planning requires clear objectives to develop students' discipline, including structured material selection, scheduling, and activities that instill responsibility. Activities should be adapted to the school's needs and student characteristics for effectiveness. Programs such as camping and drill exercises promote discipline through time management and self-control. Evaluation assesses behavioral changes in compliance, punctuality, and responsibility. Additionally, social and leadership aspects are considered essential in shaping discipline, serving as the basis for improving Scouting activities.